Friends call me bat [large type] - Colt, Paul (Wheeler Publishing large print Western, 2019)
"Known for his historical fiction and Great Western Detective League series, Colt (Sycamore Promises, 2018) uses an inventive narrative format to deftly weave adventure, nostalgia, American history, and biography together. Colt imagines real-life friends Damon Runyon (famed journalist and short story author) and Bartholemew William Barclay ""Bat"" Masterson (larger-than-life buffalo hunter, lawman, professional gambler, and boxing aficionado) reminiscing at various New York City steakhouses and delicatessens. Masterson looks back on his youth, recounting his exploits across the West and loyal friendships with larger-than-life personalities like Wyatt Earp and Theodore Roosevelt. In one vignette, Masterson details how sharpshooter Bill Tilghman took out a mounted Indian from nearly a mile away during the Second Battle of Adobe Walls. Runyon drinks it all in; these yarns help develop the Nathan Detroit character for his musical, Guys and Dolls. Masterson, in Colt's novel as in history, describes the West as it evolves from a wild frontier to a civilized land, using evocative, unrestrained language that conjures visions of the past seen only on the silver"--